Frontoethmoidal Encephalomeningocele Revisited : The Convenience Of Teamwork Approach, A CaseSeries - Kusumastuti, Nadia; Handayani, Siti; Hatibie, Mendy; Diah, Enrina; Bangun, Kristaninta (Lingkar Studi Bedah Plastik Foundation, 2012)
Background: Frontoethmoidal encephalomeningocele (FEEM) is a congenital defect of the skull which poses many problems to the patient as it results in many craniofacial and neural morbidities. While recently surgical correction of this disease is done in a single-stage procedure, many in Indonesia still perform twostage surgery which bears more risks and is technically difficult to achieve good aesthetic results. This case series intend to assess the feasibility and convenience of teamwork approach between plastic surgeon and neurosurgeon in correcting FEEM in a single-stage operation. Methods:We reviewed 8 patients with FEEM treated in Plastic and Reconstructive Surgery Division, Cipto Mangunkusumo Hospital Jakarta from November 2005 until March 2010. Four of the cases were secondary cases from Neurosurgery Department, and the other 4 cases were treated in single-stage operation, in teamwork with Neurosurgery Department, using the Chula technique. Results of each surgery was assessed using objective parameters, which are Intercanthal Distance (ICD) and Interorbital Distance (IOD); and also subjective parameters which is aesthetic improvement.Result: All of the patients showed significant improvements in ICD and IOD measurements. No complication was found intra and post-operatively. All patients, especially the ones treated with singlestage surgery show good aesthetic results. Conclusion: To achieve goals of defect correction and aesthetically pleasant appearance, single-stage surgery in teamwork with the neurosurgery department seems to be most suitable and convenient.